CULTURAL RESILIENCE THEORY AS AN INSTRUMENT OF MODELING HUMAN RESPONSE TO GLOBAL CLIMATE CHANGE. A CASE STUDY IN THE NORTH-WESTERN BLACK SEA REGION ON THE PLEISTOCENE-HOLOCENE BOUNDARY. - Smyntyna, Olena (Riparia, 2016)
Resilience theory was first introduced in natural sciences during the last third of twentieth century and soon gains transdiciplinary significance having demonstrated its high cognitive potential in frames of ecology, psychology, cultural studies and many other neighboring sciences dealing with studies of human response do the external challenge. Concept of cultural resilience was introduces for studies of past human response to the global climate change only during the last decade and, in spite of relatively restricted number of case studies for its verification allows to highlight many important aspect of human behavior which traditionally were underestimated in frames of other theories (as theory of adaptation, environmental stress and others). Subject of current contribution is to demonstrate of cultural resilience concept application in the context of studies of human response to the global climate change in the Northwestern Black Sea region on the Pleistocene-Holocene boundary.